2010
DOI: 10.1302/0301-620x.92b11.24452
|View full text |Cite
|
Sign up to set email alerts
|

Total ankle replacement in association with hindfoot fusion

Abstract: We report the clinical and radiological outcome of total ankle replacement performed in conjunction with hindfoot fusion or in isolation. Between May 2003 and June 2008, 60 ankles were treated with total ankle replacement with either subtalar or triple fusion, and the results were compared with a control group of 288 ankles treated with total ankle replacement alone. After the mean follow-up of 39.5 months (12 to 73), the ankles with hindfoot fusion showed significant improvement in the mean visual analogue sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
4
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 40 publications
2
83
4
2
Order By: Relevance
“…In contrast to the prior study by Kim et al, 16 however, overall outcome, pain relief, and implant survivorship was inferior to that of isolated TAR.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…In contrast to the prior study by Kim et al, 16 however, overall outcome, pain relief, and implant survivorship was inferior to that of isolated TAR.…”
Section: Discussioncontrasting
confidence: 94%
“…7,9,16,19,22 Furthermore, any compromise of the vascularity of the talus could lead to early component subsidence and malposition. 16 Finally, there is no consensus as to the timing of these procedures, either staged or synchronous, or whether triple arthrodeses confer a greater risk of adverse events than less complete hindfoot fusions. 16 One series has shown that at midterm follow-up, hindfoot fusion in association with ipsilateral TAR has minimal adverse effects with clinical and radiographic outcomes similar to that of primary TAR alone.…”
Section: Foot and Ankle Internationalmentioning
confidence: 99%
See 2 more Smart Citations
“…Although successful subtalar joint arthrodesis provides pain relief, resultant alterations in ankle biomechanics need to be considered carefully given the possibility that this procedure may predispose the remaining hindfoot and ankle to accelerated degenerative changes [8,19,21,23,25]. The clinical association among subtalar joint arthrodesis, double (subtalar and talonavicular), and triple (subtalar, talonavicular, and calcaneocuboid) arthrodeses with progressive ankle degeneration is evident in medium-to long-term clinical studies [13,18,24].…”
Section: Introductionmentioning
confidence: 99%